2020
DOI: 10.20944/preprints202010.0066.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grapevine – Downy Mildew <em>Rendez-Vous</em>: Proteome Analysis of the First Hours of an Incompatible Interaction

Abstract: Grapevine is one of the most relevant crops in the world being used for economically important products such as wine. Yet, relevant grapevine cultivars are heavily affected by diseases such as the downy mildew disease caused by Plasmopara viticola. Improvements on grapevine resistance are made mainly by breeding techniques where resistance traits are introgressed into cultivars with desired grape characteristics. However, there is still a lack of knowledge on how resistant or tolerant cultivars tackle the P. v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…In addition, many other studies have tested proteome changes in plant-pathogen responses. For example, several studies investigated the leaf response to biotic stress, such as Plasmopara viticola (Milli et al, 2012;Figueiredo et al, 2017;Nascimento-Gavioli et al, 2017;Santos et al, 2020;Liu et al, 2021), while another study identified potential protein markers in berries affected by noble rot (Lorenzini et al, 2015).…”
Section: Proteomicsmentioning
confidence: 99%
“…In addition, many other studies have tested proteome changes in plant-pathogen responses. For example, several studies investigated the leaf response to biotic stress, such as Plasmopara viticola (Milli et al, 2012;Figueiredo et al, 2017;Nascimento-Gavioli et al, 2017;Santos et al, 2020;Liu et al, 2021), while another study identified potential protein markers in berries affected by noble rot (Lorenzini et al, 2015).…”
Section: Proteomicsmentioning
confidence: 99%